Prevalência e fatores associados à hipertensão arterial na adolescência : estudo de coorte de nascimentos - Petracco, Andrea Mabilde (2023)
Cardiovascular diseases are related to high morbidity and mortality and represent a very high cost for the world's population, with important psychosocial and economic repercussions. The clinical manifestations of cardiovascular diseases generally occur after a long period of silent involvement. As a result, many studies have focused on assessing lifetime exposure to risk and/or protective factors and their impact on future cardiovascular events. As a result, the emphasis on the need for primary prevention is increasingly evident. For children's health, however, there is still no measurable definition of what would be good health and what would bring benefits throughout life. Most people are exposed to risk factors for cardiovascular disease during their lifetime. These risk factors differ in frequency and intensity in each population, being closely associated with the environment, which is made up of cultural, psychosocial and economic characteristics, which may favor the occurrence and combination of different exposures. Elevated blood pressure in childhood is a marker of involvement with atherosclerotic disease, and the value of its diagnosis is still not well defined in this age group. Estimating the prevalence of arterial hypertension in children and adolescents is the first step necessary to define its prevention. In addition, the identification of possible risk factors for arterial hypertension, which are more specific for this population, has a potential impact on the prevention of atherosclerotic disease and, consequently, on the reduction of brain and cardiovascular events, which have a strong impact on morbidity and mortality worldwide. . Thus, this study aims to evaluate the prevalence of arterial hypertension at 15 years of age, in the 2004 Pelotas Birth Cohort, and its potential associated factors